Takrif Kepimpinan, Ciri-Ciri Pemimpin dan Motivasi untuk Memimpin menurut Sudut Pandang Pemimpin Wanita Akar Umbi (Defining Leadership, Leader Characteristics and Motivation to Lead from the Point of View of Women’s Leader at Grassroot Level) - ROZITA IBRAHIM; MUHAMMAD RAHIMI HASAN; BAHIYAH ABDUL HAMID (MALIM: Jurnal Pengajian Umum Asia Tenggara, 2018)
New findings regarding leadership within specific context as well as differences between male and female leaders emerge as researchers from various cultural backgrounds venture into this complex and interesting field of study. Malaysian researchers have also contributed a lot in the study of leadership at the local level. However, studies regarding women leadership is still lacking especially the ones related to grassroots women leaders. Hence, a study was conducted to understand the experiences of women grassroots’ leaders. In this article, the findings from a focus group discussion with women grassroots’ leaders will be presented. The focus group discussion seek to understand some aspects of leadership based on the background and first hand experiences of the respondents. The respondents shared their views on the definition of leadership, traits of ideal leaders, motivations to become leaders and the best ways to train grassroots women leaders in order to empower them with good leadership skill.